Pengaruh Desain Produk Dan Harga Terhadap Keputusan Pembelian di Gallery Sriwijaya Palembang - Ramadhani, Nabila Putri; Lestari, Retno Budi (MDP Student Conference, 2024)
This research aims to determine the influence of product design and price on purchasing decisions at the Sriwijaya Gallery in Palembang. Respondents were buyers from Gallery Sriwijaya with a sample of 240 respondents. The results of the research are that product design and price have a positive and significant effect on purchasing decisions at Gallery Sriwijaya partially or simultaneously.